PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAN DENGAN TRANSPARANSI PERUSAHAAN SEBAGAI VARIABEL MODERATING - Amalia Ilmiani; Catur Ragil Sutrisno (Fakultas Ekonomi Universitas Pekalongan, 2015)
This study aims to identify and analyze the effect of tax avoidance on firm value with the company transparencyas a moderating variable. The study population used is the manufacturing companies listed in Indonesia StockExchange. Sampling method using purposive sampling and normal samples obtained by 50 years of researchwith 2010 – 2012. Testing hypotheses using multiple regression analysis. Based on test results, obtainedinformation that the variable tax avoidance is a significant negative effect on firm value, which means that thehigher the tax avoidance, the lower the value of the company. Variable transparency able to moderate therelationship between tax avoidance on firm value. The positive influence shows that the higher the level oftransparency in corporate tax evasion, the value of the company will be increased . Keywords : tax avoidance, transparency, firm value